2020
DOI: 10.34133/2020/2402961
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Chronic Diseases and Acute Organ Injuries Are Strongly Correlated with Disease Severity and Mortality among COVID-19 Patients: A Systemic Review and Meta-Analysis

Abstract: The recent outbreak of COVID-19 has been rapidly spreading on a global scale. To date, there is no specific vaccine against the causative virus, SARS-CoV-2, nor is there an effective medicine for treating COVID-19, thus raising concerns with respect to the effect of risk factors such as clinical course and pathophysiological parameters on disease severity and outcome in patients with COVID-19. By extracting and analyzing all available published clinical data, we identified several major clinical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
265
4
33

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(355 citation statements)
references
References 113 publications
32
265
4
33
Order By: Relevance
“…For comorbidities, we found CVD, HTN and DM to be signi cantly associated with ICU mortality, which is consistent with ndings by a review that identi ed these same comorbidities to be correlated with disease severity and ICU admissions [49]. Separately, Wang et al also found HTM, DM, and CVD to correlate with COVID-19 severity and mortality [54].…”
Section: Discussionsupporting
confidence: 90%
“…For comorbidities, we found CVD, HTN and DM to be signi cantly associated with ICU mortality, which is consistent with ndings by a review that identi ed these same comorbidities to be correlated with disease severity and ICU admissions [49]. Separately, Wang et al also found HTM, DM, and CVD to correlate with COVID-19 severity and mortality [54].…”
Section: Discussionsupporting
confidence: 90%
“…Compared to COVID-19 patients without preexisting comorbidities, those with CVD, CKD, COPD or liver disease had greater excess death. The strength of correlation between different comorbidities and the prognosis, however, was inconsistent when compared with the previous researches (2,5,24). We do not nd signi cant risk increase in hypertension and diabetes.…”
Section: Discussioncontrasting
confidence: 96%
“…Ten percent of the sample had previously diagnosed chronic diseases, and systematic reviews demonstrated that one major determent of COVID-19 severity is preexisting chronic condition, which con rms the results of this study (22,23).…”
Section: Discussionsupporting
confidence: 85%